Unlocking potential: Integrating pronunciation into business instruction to inspire students and strengthen content teachers - Kanoksilpatham, Budsaba; Pariwatnanont, Chongrug (Studies in English Language and Education, 2024)
Integrating content and language instruction has gained popularity worldwide because it allows students to improve their content knowledge while concurrently honing their language skills. Although this approach seems beneficial in principle, it can be quite demanding, particularly on the content teachers part in practice. This study aims to examine the effect of language instruction integrated into a content class at a university in Thailand. Based on a content teachers voluntary participation, a class of business students (N = 52) were exposed to 5-8 minutes of English word stress instruction in eight business lessons spanning over the entire course. A similar 40 business words for the pretest and post-test were administered at the beginning and toward the end of the course. Subsequently, a focus group discussion of six students was conducted to elicit the students attitudes toward such integrated instruction. The analysis of both quantitative and qualitative data shows that integrating pronunciation instruction with content instruction can be beneficial. Cognitively, the students word stress placement skills have substantially improved, as determined by a high value of the t-test. Psychologically, the students had positive attitudes, greater motivation to learn English, higher engagement in the lessons, and more confidence in speaking English. Overall, the study demonstrates that pronunciation instruction minimally integrated with content instruction could lead to immense pronunciation success. The study has important implications for English language educators who seek to effectively integrate pronunciation instruction into their content instruction programs, benefiting both students and content teachers.